In the absence of hard data, Is soft data better than no data at all?. (4th March 2018) - Dalgarno, Phil
Abstract: Where total anonymity and confidentiality were previously respected in drug research, a tendency towards the provision of "hard" data such as verifiable personal details seriously disadvantages researchers working with "hidden groups" who use drugs in a relatively problem free way. This particularly applies to those who use substances generally regarded as highly addictive and problematic, such as heroin. Funding for a follow-up to an earlier research project was sought; the original investigated non-problematic heroin users, whereas the chief aim of the follow-up was to examine "resilience" to the problems commonly associated with the use of heroin. An illustration of attempting to put the gathering of "hard" verifiable data into action is presented here along with the immediate consequences. Unsurprisingly, the response of potential participants to the idea of providing personal details was largely negative, as the perceived consequences of being "outed" as a heroin user were generally regarded as worse than any of the issues associated with the use of the drug itself. An irony of the situation is that this "resilience" may be due to participant refusal to compromise their anonymity. This raises some obvious ethical issues. A number of potential longer term consequences on substance use/misuse research are also discussed.